Improved Ventricular Repolarisation with Long-Term Continuous Positive Airway Pressure in Heart Failure Patients with Obstructive Sleep Apnoea: A Prospective Randomised Controlled Trial - Gilman, Matthew P.; Kim, Han; Hood, Roberta; Chauhan, Vijay S.; Bradley, Thomas D. (Trinity Student Medical Journal, 2008)
Background: Obstructive sleep apnoea (OSA) has a high prevalence in patients with congestive heart failure (CHF) and contributes to its progression. Periodic obstructive events subject the heart to recurrent episodes of nocturnal hypoxia and harmful effects on the autonomic nervous system, which can predispose the heart to ventricular arrhythmias. It has been shown that treatment with continuous positive airway pressure (CPAP) can improve cardiac and autonomic function in CHF patients with OSA. These improvements include increased left ventricular ejection fraction (LVEF), an increase in vagal tone, and a decrease in sympathetic drive. As autonomic tone, hypoxia, and afterload are known to modulate ventricular repolarisation (which is a determinant of malignant ventricular arrhythmias in heart failure patients), in this study we hypothesised that CPAP would improve ventricular repolarisation. The temporal lability of ventricular repolarisation can be measured using beat-to-beat QT variability (QTVI). Methods: Eighteen patients with CHF (LVEF <45%) and OSA (apnoeas and hypopnoeas index (AHI) ≥20) underwent baseline polysomnography and echocardiography. QTVI was assessed from an electrocardiographic lead I during stage 2 sleep. The patients were then randomised to a control group (N=7, AHI=45.0 ± 15.0), or a CPAP treated group (N=11, AHI=40.2 ± 22.8) for one month, after which the above protocol was repeated. Results: OSA was unchanged in the control group, but was alleviated in the CPAP group. The control group did not experience any significant changes in QTVI. In contrast, the CPAP treated group experienced a significant decrease in QTVI after one month (-0.37 ± 0.82 to -0.91 ± 0.55, P=0.006). This decrease in QTVI was significantly different between the two groups (P=0.021). Conclusions: These findings indicate that in patients with CHF, treatment of coexisting OSA by CPAP improves ventricular repolarisation, which could reduce the risk of malignant arrhythmias.